2018
DOI: 10.48084/etasr.1743
|View full text |Cite
|
Sign up to set email alerts
|

Wear Analysis of a Ti-5Al-3V-2.5Fe Alloy Using a Factorial Design Approach and Fractal Geometry

Abstract: This paper describes the application of the full factorial experimental design technique to confirm the significance of the factors affecting the wear behavior of a recycled Ti-5Al-3V-2.5Fe alloy with a minimum number of experiments. The fractal theory has been used to describe the worn surface state and to investigate the relationship between the fractal dimensions and the surface morphology. The experiments of the sliding wear have been performed under stresses in the range of 1-5 MPa and within sliding velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…In the images taken for the 8 specimens at the same magnification, the dark regions show the α phase, while the light regions present the β phase [25]. The presence of delamination wear, abrasion and debris in the SEM pictures of Ti-6Al-4V is in accordance with the test results of other titanium alloy testing [26]. IV.…”
Section: E Scanning Electron Microscopy (Sem)supporting
confidence: 81%
“…In the images taken for the 8 specimens at the same magnification, the dark regions show the α phase, while the light regions present the β phase [25]. The presence of delamination wear, abrasion and debris in the SEM pictures of Ti-6Al-4V is in accordance with the test results of other titanium alloy testing [26]. IV.…”
Section: E Scanning Electron Microscopy (Sem)supporting
confidence: 81%
“…It has been shown in previous studies that worn surfaces contain information that can be used in prediction of operational health status of components and machines [1][2][3][4]. However, this information was lacking of details and hence its utilization is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Worn surfaces of titanium alloys were generated during tests conducted at different sliding distances and loads. 3 It was shown that the roughness of the surfaces increases monotonically with the sliding distance and stress. These findings could be of use in the estimation of wear rate in manufacturing of titanium-based products.…”
Section: Introductionmentioning
confidence: 99%
“…Visual assessment of wear surfaces has been traditionally used as a method of choice. 2,3,6 Although it can be useful, the assessment is subjective and requires highly trained experts. Thus, computer-based techniques are gradually being developed and employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation